The Impact of a Leadership Development Program on Saudi University Students’ Perception of Leadership Skills - Amani Hamdan Alghamdi; Al- Hattami (Intelektual Pustaka Media Utama, 2018)
This study was conducted to examine whether a leadership training program increases university students’ perception of leadership skills. Female students, like their male counterparts, have to play a central role in the economy of the country, regardless of the existing social constraints. Therefore, they need to be equipped with leadership skills in order to ensure that they are capable of making authentic changes in society. The survey included 42 components with seven subscales that were used to measure the following leadership skills: communication, planning, teamwork, decision-making, controlling, motivation and evaluation. The sample consisted of 36 female students who were randomly selected to participate in a two-day leadership training program at the University of Dammam. A questionnaire was distributed at the end of the program. This questionnaire was applied with the objective of estimating the students’ perception of the importance of leadership-related skills. The results demonstrate that this program significantly develops participants’ perceptions of leadership skills, as t(35) = 7.81, p less than 0.05, regardless of their area of academic specialization, their history of participation in organized social activities, any previous leadership roles that they may have held, and any previous leadership training that they may have received. The authors recommend that this study be replicated on a larger sample.